SISTEM BIKAMERAL DI LEMBAGA LEGISLATIF BERDASARKAN TUGAS DAN KEWENANGAN DEWAN PERWAKILAN DAERAH (Perbandingan dengan Amerika Serikat, Inggris, dan Argentina) - Yokotani Yokotani (PROGRESIF: Jurnal Hukum, 2017)
The role of the legislature as a representation of the people has been much improved. The duties and functions and forms of this institution are also developing which has the system of state government and the form of its state. The legislature as an institution must exist in the system of government and any state form applied in the countries of the world. But the development of the chamber that is applied by each country is sometimes different from each other despite having the same governmental system and state form